Relationship Beetwen Perception and Attitude With Visits of Mother and Toddler to Integrated Service Post - Ningsih, Rini; Ratanto, Ratanto; Wahyuni, Rahmawati; Sapto Pramono, Joko (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The communitity's role in varioss health development efforts is seen from the Communty-Based Health Efforts, which are growing rapidly in the from of Integrated Service Post. The activeness of the mother is very important in supoporting this activity. Objective: To determine the Relationship Between Perception And AttitudeWith Visits Of Mother And Toddler To Integrated Service Post at working Are of Public Health Center Long Jaringan Mahakam Ulu Distirict In 2023. Method: Quantitative descriptive research with cross sectional design. The research was conducted in March- April 2023, the sample of this research amounted to 80 mothers who visits Integrated Service Post. Result and Discussion: There is significant relationship between mother's perception and the role of cadres p-value 0.000 (p<0.05), and between mother's attidutes on Integrated Service Post 0.000 (p<0.05), and activity of mothers taking their toddlers to Integrated Service Post. Conclusions: There is relationship Between Perception And Attitude Of Mother with activity of mother to taking the toddlers to Integrated Service Post who supported by charateristics off eduction, profession, distance to the Integrated Service Post, transpotation to the Integrated Service Post and the completeness of facilities at Integrated Service Post.